The Encapsulation of Salts by Consolidants Used in Stone Conservation - Janet Berry (Papers from the Institute of Archaeology, 1994)
Stone has been used by man as a building material, and for sculpture, for thousands of years, because of its relative strength and durability. However, since the onslaught of industrialisation, the built environment has been subjected to increasing rates of decay. This has been met with a growth in conservation treatments. One of the aims of stone conservation is 10 prevent deterioration of the stone by the action of soluble salts present in the decayed stone. One approach is to encapsulate the salts in a consolidant, thereby suppressing their activity. This was one of the objectives when deeply penetrating consolidants were first investigated in the early 1970's. However, it transpired that some objects were still exhibiting efflorescence after consolidation. The aim of the work described in this paper was to undertake an investigation into the encapsulation of soluble salts by consolidants commonly used in stone conservation.
Keywords: stone; salts; conservation